PENGEMBANGAN KREATIVITAS GURU PENDIDIKAN AGAMA ISLAM MELALUI SUPERVISI AKADEMIK - Hilal Mahmud; St Muzdalifah (Institut Agama Islam Negeri (IAIN) Palopo, 2019)
This study aims to identify the role of supervisors and the teacher creativity of Islamic Education in the learning process at SMP Negeri 4 Masamba. This type of research is qualitative using interviews, observation, and study documentation in collecting data. The results showed that there were a number of roles carried out by the supervisors of Islamic Education at SMP Negeri 4 Masamba in developing teacher creativity, including: teacher and/ or school principal guidance (directing), monitoring the implementation of National Education Standards, evaluating teacher and principal performance, evaluating the results of the implementation of supervision programs at target schools, professional guidance and training programs for teachers and principals. Teacher creativity is shown in the planning and implementation of learning activities, as well as evaluating student learning outcomes.